Cassini CAPS Identification of Pickup Ion Compositions at Rhea. Issue 4 (19th February 2018) - Desai, R. T.; Taylor, S. A.; Regoli, L. H.; Coates, A. J.; Nordheim, T. A.; Cordiner, M. A.; Teolis, B. D.; Thomsen, M. F.; Johnson, R. E.; Jones, G. H.; Cowee, M. M.; Waite, J. H.
Abstract: Saturn's largest icy moon, Rhea, hosts a tenuous surface‐sputtered exosphere composed primarily of molecular oxygen and carbon dioxide. In this Letter, we examine Cassini Plasma Spectrometer velocity space distributions near Rhea and confirm that Cassini detected nongyrotropic fluxes of outflowing CO 2 + during both the R1 and R1.5 encounters. Accounting for this nongyrotropy, we show that these possess comparable along‐track densities of ∼2 × 10 −3  cm −3 . Negatively charged pickup ions, also detected during R1, are surprisingly shown as consistent with mass 26 ± 3 u which we suggest are carbon‐based compounds, such as CN −, C 2 H −, C 2 −, or HCO −, sputtered from carbonaceous material on the moon's surface. The negative ions are calculated to possess along‐track densities of ∼5 × 10 −4  cm −3 and are suggested to derive from exogenic compounds, a finding consistent with the existence of Rhea's dynamic CO2 exosphere and surprisingly low O2 sputtering yields. These pickup ions provide important context for understanding the exospheric and surface ice composition of Rhea and of other icy moons which exhibit similar characteristics. Key Points: Velocity space analysis reveals negative pickup ions at Rhea as consistent with mass 26 ± 3 u which are consequently suggested to consist of CN −, C 2 H −, C 2 −, or HCO − These carbon‐based negative ions are suggested to derive from carbonaceous material present on Rhea's surface which is exogenic in origin These results may provide insight into the unidentified trace constituents distributed throughout the icy satellites of Saturn and Jupiter